2002
DOI: 10.1097/00005537-200201000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nasal Surgery on Sleep‐Related Breathing Disorders

Abstract: We conclude that nasal surgery has a limited efficacy in the treatment of adult patients with sleep apnea. Nevertheless, nasal surgery significantly improves sleep quality and daytime sleepiness independent of the severity of obstructive sleep-related breathing disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
1
15

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 28 publications
4
122
1
15
Order By: Relevance
“…2 Surgeries included in the study were septorhinoplasty, septoplasty, septoplasty with bilateral sinus surgery, nasal tip surgery, and bilateral nasal valve surgery. They found no significant improvement in the apnea-hypopnea index (AHI) (31.6 to 28.9, P ¼ .52) or oxygen desaturation index (40.3 to 39.7, P ¼ .89), but there were significant reductions in both the Arousal Index and the Epworth Sleepiness Scale (ESS); mean ESS improved from 11.9 to 7.7 (P ¼ .0004), which represents a clinically and statistically significant improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 Surgeries included in the study were septorhinoplasty, septoplasty, septoplasty with bilateral sinus surgery, nasal tip surgery, and bilateral nasal valve surgery. They found no significant improvement in the apnea-hypopnea index (AHI) (31.6 to 28.9, P ¼ .52) or oxygen desaturation index (40.3 to 39.7, P ¼ .89), but there were significant reductions in both the Arousal Index and the Epworth Sleepiness Scale (ESS); mean ESS improved from 11.9 to 7.7 (P ¼ .0004), which represents a clinically and statistically significant improvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In total, 10 patients were studied (nine males; mean¡SD (range) 46¡5 yrs ; body mass index 27¡1.5 kg?m -2 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)). The inclusion criteria were as follows: 1) OSA syndrome [27] not yet receiving treatment; 2) clinically significant nasal obstruction (on the basis of clinical examination by M.F.…”
Section: Patientsmentioning
confidence: 99%
“…Similarly, topical nasal decongestants did not reduce OSA severity in patients with nasal obstruction [19,20], but the use of topical nasal steroids in patients with allergic rhinitis was associated with improved subjective sleep quality in adults [21] and with an improvement in apnoea-hypopnoea index (AHI) from 10.7 to 5.8 in children [22]. Nasal surgeries have also been used to treat OSA, but the results have been inconsistent and often lacked adequate objective outcome measurements [23][24][25]. However, SERIES et al [26] demonstrated that the absence of pharyngeal narrowing (as measured by the posterior airway space) in patients with OSA delineated a group with a better response to nasal surgery.…”
mentioning
confidence: 99%
“…Apesar dos resultados limitados da cirurgia nasal na cura da SAHOS, benefícios na qualidade do sono são freqüentemente observados. Verse et al 13 preconizam a realização da cirurgia nasal independentemente da gravidade da SAHOS, pois a permeabilização da cavidade nasal leva à diminuição da fragmentação do sono, com melhora na sua qualidade e na sonolência diurna.…”
Section: Discussionunclassified
“…Assim, o tratamento da SAHOS pode ser realizado de diversas formas dependendo da gravidade da doença e das alterações anatômicas da via aérea superior (VAS) e do esqueleto facial destes pacientes 7 . Tratamentos cirúrgicos diversos têm sido propostos e podem tanto envolver a correção de alterações anatômicas encontradas na faringe [8][9][10][11][12] , na cavidade nasal 13 e na base da língua 8,14,15 , como a correção de alterações do esqueleto crâ-nio facial [14][15][16][17] . Os resultados em literatura são controversos e normalmente a indicação dos procedimentos cirúrgicos está relacionada à gravidade da SAHOS e as alterações encontradas na via aérea superior e no esqueleto facial 8,13,18 .…”
Section: Introductionunclassified